Tides at the head of the bay of Fundy; from observations from the following sources: (1) Measurements by the Tidal survey in Cobequid bay in 1916; where the highest tides occur. (2) Tide levels for the baie Verte canal, Cumberland basin, 1870. (3) Observations during Admiralty chart surveys, Noel bay, 1859. - Canada. Dept. of the Naval Service.; Dawson, W. Bell (William Bell), b. 1854. (Ottawa, Can., Dept. of the Naval service, 1917)
Detached from Canada. Dept. of Naval Service. Reports on the tides and currents in Canadaian waters. Issued by the Tidal and Current Survey from 1894 to 1918. Ottawa, Can., 1918. Mode of access: Internet.